THE IMPACT OF MONETARY POLICY ON THE ECONOMY OF THE UNITED KINGDOM: A VECTOR ERROR CORRECTION MODEL (VECM) - Agbonlahor, Osasohan (European Scientific Journal, ESJ, 2014)
The paper investigatesempirically the impact of monetary policy on economic growth in the United Kingdom. The study uses time-series data over a study period spanning from 1940-2012. The impacts of each of the endogenous variables are investigated using the Vector Error Correction Model (VECM). The study shows that a long run relationship exists among the monetary variables. Specifically, it finds that the inflationary rate and money supply are significant monetary policy instruments that drive growth in the United Kingdom. It therefore recommends that the UK policy makers focus on boosting macroeconomic performance by ensuring that growth in money supply is proportional to the growth in real Gross Domestic Product.